(untitled) (The Pakistan Development Review, 1995)
Because of its potential to disrupt economic development, it is necessary to understand the dynamics of ethnic conflict in the contemporary world. A prevalent trend in the study of ethnicity is to focus on the creation and/or maintenance of ethnic identities and mobilisation on the basis of those identities as groups compete for resources, opportunities, or political power in the context of the nation-state [Barth (1969); Brass (1985); Comaroff (1987); Mumtaz (1990)]. In this approach, an ethnic group’s distinguishing markers-language, custom, dress, etc.-are treated less as manifestations of tradition which define or create the group and more as arenas of negotiation and contestation in which people strive to realise their practical and symbolic interests. This happens as individuals or families, pursuing their livelihoods with the skills and resources available to them, find (or create) opportunities or obstacles which appear to be based on’ ethnic criteria. The state can intensify this process as it uses positive or negative discrimination in order to achieve some desired distribution of wealth and opportunity. In turn, political leadership becomes a key in realising the experience of shared ethnic interests. Leadership develops as a kind of dual legitimation process, i.e., as individuals or organisations seek to be accepted as spokesmen both by members of the group itself and by outsiders.